Climate information services enhance farmers’ resilience to climate change: Impacts on agricultural productivity - Tamru, Seneshaw; Hansen, James; Zebiak, Stephen; Tesfaye, Abonesh; Minten, Bart; Demissie, Teferi; Radeny, Maren A.O.; Tesfaye, Kindie; Solomon, Dawit (Elsevier, 2025)
Ethiopia is a climate “hotspot” where the variable and changing climate periodically threatens agricultural production, food security, and human well-being. Using two-rounds of Feed the Future program survey data that cover 3,799 farming households in five major regions in Ethiopia, and employing panel data estimation methods, we analyze the potential impact of weather and climate services (WCS) on agricultural productivity and farmers’ resilience in Ethiopia. We found that access to WCS increases the productivity of maize and wheat crops by 27 % and 17 %, respectively. These estimates are comparable to or higher than conventional yield-increasing production technologies such as fertilizer and improved seeds. Despite such a strong productivity effect, access to WCS is limited to only 18 % of the surveyed farmers. This study adds to the existing body of evidence on the significant positive impact of WCS, and affirms the importance of weather and climate information service products to enhance farmers’ resilience to climate risk. Further analyses are needed to estimate the value to Ethiopia’s smallholder farmers, especially those who are most vulnerable to climate-related hazards, of increasing investment in improving seasonal climate forecasts, mainstreaming weather and climate services in the agricultural extension system, including through National Framework for Climate Services (NFCS), and supporting farmer decision-making with climate-informed digital advisory tools and training.